2019
DOI: 10.3758/s13414-019-01810-8
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-dependent sensitivity explains the accuracy of decisions when cues are separated with a gap

Abstract: Most decisions require information gathering from a stimulus presented with different gaps.Indeed, the brain process of this integration is rarely ambiguous. Recently, it has been claimed that humans can optimally integrate the information of two discrete pulses independent of the temporal gap between them. Interestingly, subjects' performance on such a task, with two discrete pulses, is superior to what a perfect accumulator can predict. Although numerous neuronal and descriptive models have been proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
2
15
2
Order By: Relevance
“…In other words, spikes generated in different time points which are indicators of the edge's strength and the strength of the pre-learned patterns in the input image, are not redundant and they can improve the categorization performance. This improvement in performance as a result of longer stimulus duration, is in line with results in behavioral studies 29 . It should be noted that, in this analysis, crossing the bound cannot be the decision rule because we forced the model to decide about input stimulus at different time points, no matter if any of the accumulators cross the bound or not.…”
Section: Generated Spikes Convey Information About the Stimuli Classesupporting
confidence: 89%
See 1 more Smart Citation
“…In other words, spikes generated in different time points which are indicators of the edge's strength and the strength of the pre-learned patterns in the input image, are not redundant and they can improve the categorization performance. This improvement in performance as a result of longer stimulus duration, is in line with results in behavioral studies 29 . It should be noted that, in this analysis, crossing the bound cannot be the decision rule because we forced the model to decide about input stimulus at different time points, no matter if any of the accumulators cross the bound or not.…”
Section: Generated Spikes Convey Information About the Stimuli Classesupporting
confidence: 89%
“…The input category will be recognized as soon as an accumulator reaches a threshold. This accumulation to the bound mechanism of decision making is a well-known biologically plausible decision-making model 2,[27][28][29][30] . Results show that the temporal representation of the input stimuli is informative, since it can explain human reaction time as well as the accuracy, in an object recognition task.…”
mentioning
confidence: 99%
“…The two pulses separated by up to 1 s supported a level of confidence that was indistinguishable from a pair of pulses separated by no gap. Direct comparison between single-pulse and double-pulse trials, along with previous studies Tohidi-Moghaddam et al, 2019), showed that participants' accuracy significantly differed (t(11490) = -3.09, p < .05, 95% CI = [-.08, -.02], Cohen's d = .11). However, in double-pulse trials participants were not more confident comparing to single-pulse trials (t(11490) = 1.35, p = .18, 95% CI = [-.01, .06], Cohen's d = -.05).…”
Section: Behavioral Resultsmentioning
confidence: 63%
“…Finally, how implicit markers of confidence -response-time, CPP and pupillometry-change after receiving separated pieces of information. Here, to clarify confidence, we required observers to make a two-alternative decision after viewing either one (single-pulse) or two (double-pulse) motion pulses separated by four various temporal gaps (similar to (Kiani et al, 2013;Tohidi-Moghaddam et al, 2019)). We performed several logistic regression models to measure the impact of stimulus characteristics on confidence.…”
Section: Confidence and Accuracy After Integration Of Discrete Evidencementioning
confidence: 99%
See 1 more Smart Citation